Patterns of DNA synthesis during pollen embryogenesis in henbane (The Rockefeller University Press, 1977)
Continued DNA synthesis in the generative cell nucleus, followed by mitosis and cytokinesis, results in the formation of pollen embryoids in cultured anthers of H. niger. In contrast, the nucleus of the vegetative cell undergoes no DNA synthesis after it is cut off, or synthesizes DNA only during a limited number of cell cycles. DNA synthetic patterns in the generative and vegetative cell nuclei confirm the ontogeny of embryoids described in this plant.